An estimation of quality-adjusted prices for mobile services in Korea - Wook Joon Kim; Yongkyu Kim (International Telecommunications Society (ITS), 2018)
The introduction of smartphones marked a transitional phase in the evolution of pricing for mobile communications service markets. Wireless operators migrated to supplying data centric tariffs which have characteristics that are different from the old, which makes it ever more difficult for conventional price indexes to reflect consumers' valuation in a timely and precise manner. However, little information has been known about the mobile service price developments embodying such technological change, although they are critical to our understanding of economic benefits from communications technologies. We consider service quality change to adjust the price of mobile service products. To the extent which prices are determined by quality change, taking into consideration tariffs' usage allowances practiced by operators is essential if we are to understand how prices change in the era of smartphones. We use hedonic regression techniques to estimate quality-adjusted price indexes for smartphone communication service products 2010-2017 in Korea. We investigate a total of 209 mobile plan observations sold by the major operators, where the focus is on tracing down the introduction of new plans as well as the variations in prices and characteristics over the periods concerned. We compute the weight of each observation by using a set of combined quantity data gathered from the Ministry of Science and ICT of Korea and KMPSS. The study reports the weighted averages of prices and characteristics, and chooses to implement the two-year adjacent non-linear regressions to construct estimated quality-adjusted price indices for mobile services. The results show a price decline of 8.1% per year over the periods, as specifying the timing and size of price movements across operators. We briefly discuss findings of the study to provide policy recommendations.
Keywords: 330; hedonic price index; mobile service; smartphone; substitution; quantity weights; pricing; competition